The Relationship of Medication Adherence in Type 2 Diabetes Mellitus Patients with HbA1c Profile at Mataram University - Hudhori, Syalsa; Wardani, Indah Sapta; Isnaeni, Wilya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Type 2 Diabetes Mellitus (DM) requires optimal glycemic control. Medication adherence is key to achieving HbA1c targets, but local data at Universitas Mataram Hospital is still limited. This study aimed to analyze the relationship between medication adherence and HbA1c profiles in type 2 DM patients. An analytical cross-sectional study was conducted in May 2025 with 40 randomly selected samples. Adherence was measured using the MMAS-8 questionnaire, and HbA1c data came from medical records. Data analysis used the Chi-Square test. Results showed 50% of subjects were adherent and 50% were non-adherent. Regarding glycemic control, 70% had controlled HbA1c. Statistical analysis found no significant relationship between adherence and HbA1c profile (p-value = 0.490). However, a proportional trend showed the adherent group had a higher percentage of HbA1c control (75%) than the non-adherent group (65%). Conclusion, there was no statistically significant relationship between medication adherence and HbA1c profiles. Despite this, the observed clinical trend indicates that adherence remains an important factor to consider in DM management, alongside other determinants like diet and physical activity.